Fine-structure deletion analysis of the transcriptional silencer of the proU operon of Salmonella typhimurium. - Fletcher, S A (1995)
Transcriptional control of the osmotically regulated proU operon of Salmonella typhimurium is mediated in part by a transcriptional silencer downstream from the promoter (D.G. Overdier and L.N. Csonka, Proc. Natl. Acad. Sci. USA 89:3140-3144, 1992). We carried out a fine-structure deletion analysis to determine the structure and the position of the silencer, which demonstrated that this regulatory element is located between nucleotide positions +73 to +274 downstream from the transcription start site. The silencer appears to be made up of a number of components which have cumulative negative regulatory effects. Deletions or insertions of short nucleotide sequences (< 40 bp) between the proU promoter and the silencer do not disrupt repression exerted by the silencer, but long insertions (> or = 0.8 kbp) result in a high level of expression from the proU promoter, similar to that imparted by deletion of the entire silencer. The general DNA-binding protein H-NS is required for the full range of repression of the proU operon in media of low osmolality. Although in the presence of the silencer hns mutations increased basal expression from the proU promoter three- to sixfold, in the absence of the silencer they did not result in a substantial increase in basal expression from the proU promoter. Furthermore, deletion of the silencer in hns+ background was up to 10-fold more effective in increasing basal expression from the proU promoter than the hns mutations. These results indicate that osmotic control of the proU operon is dependent of some factor besides H-NS. We propose that the transcriptional regulation of this operon is effected in media of low osmolality by a protein which makes the promoter inaccessible to RNA polymerase by forming a complex containing the proU promoter and silencer.